2018
DOI: 10.1016/j.str.2018.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Activity in the p53 Family Depends on the Organization of the Transactivation Domain

Abstract: Despite high sequence homology among the p53 family members, the regulation of their transactivation potential is based on strikingly different mechanisms. Previous studies revealed that the activity of TAp63α is regulated via an autoinhibitory mechanism that keeps inactive TAp63α in a dimeric conformation. While all p73 isoforms are constitutive tetramers, their basal activity is much lower compared with tetrameric TAp63. We show that the dimeric state of TAp63α not only reduces DNA binding affinity, but also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(45 citation statements)
references
References 37 publications
1
44
0
Order By: Relevance
“…To experimentally investigate these predictions we mutated the residues most likely important for transactivation to alanines and investigated their influence on the transactivation potential of TAp63γ, TA*p63γ, and GTAp63γ, each carrying the FWL mutations. As expected TAp63γ FWL is inactive due to the importance of these three aa for interaction with p300 16 , while the two other FWL mutants still show distinct induction of the promotor. Only simultaneous mutation of the additional two motifs predicted in the TA*/GTA and GTA* peptides leads to a completely inactive protein (Fig.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…To experimentally investigate these predictions we mutated the residues most likely important for transactivation to alanines and investigated their influence on the transactivation potential of TAp63γ, TA*p63γ, and GTAp63γ, each carrying the FWL mutations. As expected TAp63γ FWL is inactive due to the importance of these three aa for interaction with p300 16 , while the two other FWL mutants still show distinct induction of the promotor. Only simultaneous mutation of the additional two motifs predicted in the TA*/GTA and GTA* peptides leads to a completely inactive protein (Fig.…”
Section: Resultssupporting
confidence: 76%
“…In earlier studies we had shown that inhibition of the transcriptional activity of TAp63α is mechanistically based on the formation of a closed and only dimeric state with decreased affinity to both the DNA 6,8 and coactivators such as p300 16 . To investigate if TA*p63α and GTAp63α adopt a closed, dimeric conformation as well, we expressed both isoforms and TAp63α as control in H1299 cells and analyzed their oligomeric state by Blue-Native (BN)-PAGE.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The coactivation mode of p63 (ΔNp63α) was distinguished from the well-described transactivation mode of p53 and TA-p63, because the coactivation required stronger induction of β-catenin and functional WREs to which TCF/LEF proteins bind. The TA domain of TA-p63 isoforms interacts with p300 with a stretch conserved among p53 family proteins, (Figure 3 D ) for transcriptional activation [7]. In the case of TAp63α, interestingly, the ‘transcription inhibitory’ domain (TID) at the extremely C-terminus of the α-domain directly binds to the TA domain to block the transactivating function [32], [33], [34].…”
Section: Discussionmentioning
confidence: 99%
“…The TA domain of p63 has a single p300-binding site, whose sequences are conserved among p53 family proteins, to transactivate target genes [7]. In contrast, ΔN-p63 proteins lack the entire TA domain and instead have ΔN-specific sequences of only 14 amino acid residues.…”
Section: Introductionmentioning
confidence: 99%